PERANCANGAN DAN PEMBUATAN FILM PENDEK ANIMASI 2 DIMENSI “TIMUN MAS” - Dedi Eko Nurcahyo (Institut Seni Indonesia Padangpanjang, 2022)
ABSTRACTFilm is a medium of information and mass communication that is quite effective, because films can build public opinion with various formats of impressions and forms of presentation in conveying messages through a story that is audio-visual or vivid images and sounds. Timun Mas is a well-known folk tale in Java. In this study, the story of Timun Mas was repackaged into a 2-dimensional animated short film. Timun mas animation production methods include Pre-Production, Production, and Post-Production. The results of this animation design are in the form of scenarios, storyboards, characters, and an animated short film entitled